HUBUNGAN SIKAP AKSEPTOR KB DENGAN PEMILIHAN METODE KONTRASEPSI IMPLAN DI PUSKESMAS BATU AJI KOTA BATAM - Berutu, Dorta; Yunifitri, Astri (Universitas Batam, 2019)
The attitude of a married couple on family planning acceptors and kinds of the contraceptive implant they take is potentially influenced by several factors, for instance the experience, socio-cultural issues, beliefs, and the facilities. To acquire a positive attitude about family planning requires a good attitude of married women and men toward it as well. Attitude has been seen as a very important realm in shaping someone’s behavior. The purpose of this research is to analyze the correlation of fertile couples’ attitude toward the family planning acceptors and their decision to take such contraceptive implant as an effort for birth controlling. This research is correlational study with cross sectional approach. The population investigated is all fertile age women documented as the family planning acceptor participants in BatuAji Health Center, which is further taken 58 respondents to be the sample through accidental sampling method. The data was collected using questionnaires and was analyzed with Chi Square statistical test. The result presents from 30 respondents with positive attitude, 20 respondents (66.7%) choose contraceptive implant and 10 respondents (33.3%) did not choose any contraceptive implant for birth control. On the other hand, it is reported that from 28 respondents with negative attitude, 8 respondents (28.6%) take contraceptive implant yet, 20 respondents (71.4%) do not take any. As the Chi Square test ensues p-value of 0.005<0.05, it can be confirmed that there is a correlation between the fertile age couples attitude on family planning acceptors with their decision to take certain contraceptive implant methods.